HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR MUATAN PEMBELAJARAN IPA SISWA KELAS TINGGI DI SEKOLAH DASAR KABUPATEN PANGKEP - Muslimin; Nurul Mukhlisa; Miftahul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This quantitative correlational research aims to determine whether students' science learning outcomes at Pangkep Regency Elementary Schools are related to their learning motivation. The independent variable (learning motivation) and the dependent variable (science learning outcomes) are the two variables in this research. A sample of 100 students from a population of 36,794 elementary school students in Pangkep Regency was used in this research. For the 2023–2024 academic year, data was collected through questionnaires and midterm exam scores for science subjects. Data were analyzed using correlation methods and significance tests. The results of descriptive statistical analysis show that student learning motivation is in the high category with a percentage reaching 54%. On the other hand, science learning results show a very good score of 78%. H0 is rejected and H1 is accepted after correlation analysis produces a significance value of 0.002, which is less than 0.05. The low correlation between student learning motivation and learning outcomes is shown by a correlation coefficient of 0.227.